Serum 4-hydroxynonenal associates with the recurrence of patients with primary cerebral infarction - Liu, Xingliang; Bai, Meiling; Fan, Lei; Lou, Zhan (Frontiers in Cellular Neuroscience, 2022)
Background: 4-hydroxynonenal (4-HNE) is an unsaturated aldehyde produced, was found to be associated with aspirin resistance, a risk factor for recurrent cerebral infarction. but its effect on recurrent cerebral infarction is less-defined. We designed this study to investigate the association of 4-HNE and increased risk of recurrent cerebral infarct. Methods: We recruited 189 patients with primary cerebral infarction from 2017 to 2019. According to the recurrence of cerebral infarction during the 3-year follow-up period, they were divided into 2 groups, namely the non-recurrence group (n=93) and the recurrence group (n=96). of patients, and analyzed the risk factors affecting the recurrence of primary cerebral infarction and the predictive value of serum 4-HNE on the recurrence of cerebral infarction. Results: The levels of serum 4-HNE in patients of recurrence group was significantly higher than that in patients of non-recurrence group. There was a positive correlation between serum 4-HNE levels and the serum levels of triglyceride (r = 0.448, P=0.008), LDL-C (r=0.442, P=0.002) in primary cerebral infarction patients. Cox proportional hazards modeling showed that elevated serum 4-HNE levels (HR = 2.631, 95%CI:1.639-4.413, P<0.001) was risk factors for recurrent cerebral infarction. And when the cut-off value of serum 4-HNE was set at 42.34 ng/mL, the sensitivity and specificity of serum 4-HNE in predicting recurrent cerebral infarction were 79.20% and 52.70%, respectively. Conclusion: Serum 4-hydroxynonenal increases the risk of recurrence in patients with primary cerebral infarction.